2020
DOI: 10.1017/s1041610220000903
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of ketamine for the treatment of depression among older adults

Abstract: Objective: To review the currently available data on the use of ketamine in the treatment of depression among older adults from randomized controlled studies. Design: Randomized controlled trials. Setting: Variable. Participants: 60 years and older with depression. Intervention: Ketamine. Measurements: Change in Montgomery–Asberg Depression Rating Scale (MADRS) scores. Results: Two studies met the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 71 publications
0
5
0
1
Order By: Relevance
“…None of the RCTs or existing systematic reviews of psychological treatment reported on adverse events, but there was no pattern of effects indicating an elevated risk of harm. For the harms of pharmacologic treatment, 3 RCTs (eTable 9 in the Supplement) and 8 existing systematic reviews addressing medications other than antidepressants (eTable 11 in the Supplement) were included . Harms of antidepressants are addressed in a separate publication .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the RCTs or existing systematic reviews of psychological treatment reported on adverse events, but there was no pattern of effects indicating an elevated risk of harm. For the harms of pharmacologic treatment, 3 RCTs (eTable 9 in the Supplement) and 8 existing systematic reviews addressing medications other than antidepressants (eTable 11 in the Supplement) were included . Harms of antidepressants are addressed in a separate publication .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-six trials (reported in 36 publications) among primary care patients (eTables 8-9 in the Supplement) and 18 existing systematic reviews (not limited to primary care populations) (eTables 10-11 in the Supplement) addressed treatment for anxiety. Twenty-four of the included RCTs (n = 5307) examined psychological interventions and 2 (n = 423) examined pharmacological interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, with specialist assessment, this remains a viable treatment option. Others: there are several other possible treatment options that are either currently available or being investigated. These include transcranial magnetic stimulation, 23 ketamine, esketamine, 24 bupropion augmentation 25 (listed among first-line choices by the Maudsley prescribing guidelines 9 ), thyroid hormone, 26 deep brain stimulation, 27 vagus nerve stimulation, 28 psilocybin 29 and anti-inflammatories. 30 …”
Section: Discussionmentioning
confidence: 99%
“…41 Όσον αφορά ασθενείς με κατάθλιψη με ηλικία μεγαλύτερη των 60 ετών φαίνεται πως η θεραπεία με κεταμίνη έχει συγκρίσιμη αποτελεσματικότητα με την αντίστοιχη του γενικού πληθυσμού, είναι καλά ανεκτή και οι αναμενόμενες ανεπιθύμητες ενέργειες ήπιες και παροδικές, ωστόσο το συμπέρασμα αυτό βασίζεται ακόμη σε μικρό αριθμό μελετών οι οποίες μάλιστα δεν είναι σχεδιασμένες αποκλειστικά για εκτίμηση ασθενών με ΔΚ. 42 Επαναλαμβανόμενες IV χορηγήσεις σε ασθενείς ηλικίας ίση ή μεγαλύτερη των 60 ετών με ανθεκτική στη θεραπεία κατάθλιψη συσχετίστηκαν με παροδική αλλά απαιτούσα επείγουσα αντιμετώπιση αρτηριακή υπέρταση (ΑΥ), ενώ η συχνότερη ανεπιθύμητη ενέργεια σε αυτήν την ηλικιακή ομάδα φαίνεται να είναι η υπνηλία. 43 Ανεπιθύμητες ενέργειες της κεταμίνης Από το φάσμα των ανεπιθύμητων ενεργειών της κεταμίνης ιδιαίτερες ανησυχίες έχουν ανακύψει αναφορικά με τον κίνδυνο κατάχρησης-εξάρτησης, τα αποσυνδετικά συμπτώματα καθώς και τον δυνητικό κίνδυνο τοξικής νευρωνικής διέγερσης με επακόλουθη νευρωνική βλάβη κατά τη χορήγηση υψηλότερων δόσεων σε επαναληπτική βάση.…”
Section: αποτελεσματικότητα έναντι της αυτοκτονικότηταςunclassified